Digital Transformation Strategies for Enhancing Transparency and Efficiency in Indonesian Local Government Administration: A Multi-Document Triangulation and Thematic Maturity Analysis - Suraya Murcitaningrum; Yorman (Lembaga Bale Literasi, 2026)
This study examines digital transformation strategies that enhance transparency and efficiency in Indonesian local government administration and their contribution to good governance and Pancasila-based governance values through a reflexive thematic analysis of 127 official documents (2018–2025). Employing mixed-document triangulation and NVivo-Gephi network analytics, this research identifies three primary strategy clusters: roadmap-based planning (maturity 4.27), modular service orchestration (3.68), and platform interoperability (2.91), forming a Digital Governance Flywheel with transparency as a keystone mechanism (betweenness centrality 0.41). Quantitative findings reveal an 82% reduction in service cycles (d=2.67), an 89% improvement in public information access (d=2.14), and a 67% reduction in corruption risk, yielding a Digital Governance Contribution Index (DGCI) composite of 0.84 (Cronbach's ?=0.92). The findings demonstrate that digital governance not only strengthens administrative efficiency but also reinforces the ethical and normative foundations of governance aligned with Pancasila principles, particularly transparency, accountability, social justice, and participatory public administration. Dominant barriers include system fragmentation (?=-0.72) and digital illiteracy (?=-0.59), counteracted by political commitment (?=0.67). Policy implications encompass National API Standards, 3-tier ASN certification, maturity-linked fiscal federalism (+20% transfers for DGCI?0.80), and the establishment of the Indonesia Digital Governance Agency. Projected ROI reaches Rp 187 trillion within five years from efficiency gains (60%), corruption savings (28%), and service expansion (12%). Addressing evidence gaps in federal developing contexts, this research contributes the DGCI 2.0 instrument and the Indonesia Digital Federalism Template as a framework for strengthening Pancasila-oriented digital governance and ASEAN benchmarking.